Matruj baby massage oil: an herbal skincare massage oil for healthy growth of baby - Deshpande, Vallabh; Deshpande, Tanuja (International Journal of Contemporary Pediatrics, 2024)
Background: Baby massage is an ancient tradition of providing nurturing touch as a way of communicating and bonding with baby. The present research was based on preparation and evaluation of herbal baby massage oil which is FDA approved product named as ‘Matruj Baby Massage oil’. Methods: The Matruj baby massage oil was prepared by ancient ayurvedic method and further evaluated by different parameters. Results: The Matruj baby massage oil was appeared as transparent with intense orange colour and having pleasant odour. It doesn’t cause any irritation on baby’s skin surface. Its pH value is close to healthy baby skin surface. Acid value was found to be 2.24%. Viscosity, saponification value, specific gravity observed 0.01652 Pa.s, 135.76, 1.08662 kg/m3 respectively. Conclusions: Matruj baby massage oil is herbal based product which increases the strength, nourishes body, improves skin texture and accelerates the healthy growth and development of baby. Increased weight gain, reduced pain, enhanced attentiveness, and enhanced immune function.